EVALUASI PERTUMBUHAN TOXORHYNCHITES SPLENDENS AKIBAT SUPLEMENTASI DIET - Muhamat Muhamat (Bioscientiae, 2023)
Toxorhynchites splendens, or the giant mosquito, does not need blood for food but eats sweet substances such as honey, flower nectar, plant sap, and fruit extracts. There still needs to be more information about the nutrition of these mosquitoes; even research on the type of nutrition they prefer still needs to be improved. This study aims to determine the type of feed nutrition they prefer, describe their feeding activities, and define when they eat. The method in this study consisted of several stages, namely collecting larvae, rearing larvae, providing nutritional feed, observing mosquitoes, and analyzing data. The results showed that this kind of mosquitoes preferred the type of feed nutrition in liquids such as honey solution compared to flower plants and juices derived from fruit. They eat during the day, especially in the morning and evening. The longevity of both male and female mosquitoes is less than seven days. This study concludes that Tx. splendens can consume a solution of honey and flower nectar, but the feed nutrition cannot meet the needs of life and reproduction, so they need additional feed.